IFI16 Can Be Used as a Biomarker for Diagnosis of Renal Cell Carcinoma and Prediction of Patient Survival - Yu, Baozhong; Zheng, Xiang; Sun, Zejia; Cao, Peng; Zhang, Jiandong; Wang, Wei (Frontiers in Genetics, 2021)
The incidences of renal cell carcinoma increase in number each year and account for about 2% to 3% of all malignant tumors. Many patients have metastasis by the time of diagnosis, and their prognosis is poor. Therefore, it is essential that new diagnostic and prognostic markers for kidney cancer are identified. In this study, we assessed the potential of IFI16 as a diagnostic and prognostic marker for RCC. We analyzed the TCGA and UALCAN databases and found IFI16 to be highly expressed in ccRCC. In addition, high IFI16 levels positively correlated with lymphatic metastasis, tumor stage, and histopathological grade. Kaplan-Meier curve analysis showed that IFI16 expression was related to the prognosis of patients, and high IFI16 expression indicated a worse overall survival (p = 5.1E-0.7). Receiver operating characteristic curve analysis showed that a combination of IFI16 expression and histopathological grade improved predictive accuracy (AUC = 0.697; 95%CI: 0.628–0.765, P < 0.001). Finally, the relative levels of IFI16 in ACHN and Caki-1 cells were higher than that of HK-2 cells detected by western blotting analysis and RT-PCR. Functional tests showed that knocking down IFI16 expression inhibited migration and invasion in vitro. Therefore, IFI16 is a potential biomarker for the diagnosis and prognosis of RCC patients.